Analysis of the Business Model of a Trade and Export Enterprise on the Example of the Company "Top Grain L. T. D." ("Journal "U". Economy. Management. Finance.", 2020)
The article analyzes the specifics of the formation of logistics chains and their documentary support. We also consider the development trends of the company "Top Grain L. T. D.".
Keywords: multimodal transport; logistics chains; mode of transport; accompanying documents; development trends